The Friendship Questionnaire, autism, and gender differences: a study revisited - Felicity Sedgewick; Jenni Leppanen; Kate Tchanturia (Molecular Autism, 2019)
Abstract Background The Friendship Questionnaire (FQ) is a widely used measure of friendships in autism research and beyond. This study sought to revisit the original paper where the measure was presented, using a larger sample of both autistic and non-autistic participants to examine gender differences in scoring. It also sought to expand upon the original paper by comparing FQ results to those of the Unidimensional Relationship Closeness Scale (URCS), to examine whether there are differences in how autistic people report on their general friendships in contrast to their most significant relationships. Methods Participants were recruited for an online study, and 949 people (532 autistic, 417 non-autistic) aged between 18 and 81 took part. Participants completed a demographic questionnaire, the Autism Quotient-28, the Friendship Questionnaire, and the Unidimensional Relationship Closeness Scale. Results We used robust regressions and Pearson’s correlational analyses, conducted in R. Autistic people scored lower than non-autistic people on the FQ, and similar gender differences in the pattern of FQ scores were seen in both groups. There was a significant negative correlation between AQ and FQ scores in both groups. On the URCS, we took the data from those who rated specific close relationships and found that autistic people scored this relationship more highly than non-autistic adults did. There was a significant negative correlation between AQ and URCS scores in both groups. Also, in both groups, there was a significant positive correlation between FQ and URCS scores. Limitations The data is entirely self-report, and diagnoses could not be verified with a clinician, although AQ scores support self-identification as autistic. Also, the groups were not evenly matched on age and other demographic variables, although this was controlled for in analyses. It is also the case that more autistic than non-autistic people were unable to specify a close relationship to score on the URCS, meaning that a certain set of experiences are not represented in this data. Conclusions We conclude that our data replicates the core finding of the original FQ paper that autistic people score lower on the FQ. In contrast to that paper, however, we found that there were gender differences among the autistic population. Also, our inclusion of the URCS suggests that the intimate romantic relationships and best-friendships of autistic people can be of similar quality to those of non-autistic people, suggesting that there may be important differences in autistic people’s relations with friends in general versus close friends and romantic partners.